Artificial sweeteners and bladder cancer in Manchester, U.K., and Nagoya, Japan. - Morrison, A. S. (Nature Publishing Group, 1982)
We have evaluated the relation between cancer of the lower urinary tract ("bladder cancer") and the use of artificial sweeteners, by means of case-control studies in Manchester, U.K., and Nagoya, Japan, areas where extensive use occurred 30-40 years ago. In each area, a broadly based series of cases (555 in Manchester, 293 in Nagoya) was interviewed and a series of controls (735 in Manchester, 589 in Nagoya) chosen from the general population. A history of use of sugar substitutes primarily saccharin, was not associated with an elevated risk of bladder cancer in either study area. Risk of bladder cancer did not increase regularly with frequency or duration of use of sugar substitutes. Data on dietetic beverages were not obtained in Nagoya. This exposure was not associated with a greater risk of bladder cancer in Manchester. The results of this study suggest that use of artificial sweeteners confers little or no risk of bladder cancer.